Bild und Text auf römischen Mosaiken Intermediale Kommunikationsstrategien im Kontext der Wohnkultur des 3.-5. Jahrhunderts - Schmieder, Claudia (Materiale Textkulturen, 2022)
The combination of image and text is a central element of Roman mosaics from the third to fifth centuries. This volume is the first to present a comprehensive media studies analysis of the complex medial configuration of these artworks that views both media as equal. It reveals mosaics' communicative strategies within their spatial contexts but also in light of their social and cultural background.